Stellar management teams - Ristikangas, Vesa, 1971-; Rinne, Tapani, 1955- (Routledge, 2018)
"Management teams at all levels, and individual team members in particular, are often disengaged and disconnected from the management function itself. Statements such as, "we lack common goals or they are unclear", "I have no influence", "I am not listened to nor taken into account", and "I do not feel valued '" actually, nobody does", are commonplace. The authors argue this is because we have been entrenched in an era of guru leadership but that it must come to an end if our management teams are to rise to the topages An individual is not capable of controlling the complicated system of an organization, with its countless variables, especially in conjunction with the rapid change in both the economy and market forces, which are unpredictable and uncontrollable. No matter how talented the individual, no one person is in a position to manage this complex system alone '" not even a guru leader. The authors contend that what is needed now are resilient trendsetters who will bring about a new era of top-performing teams that together form a "collective guru", which they refer to as a Stellar Management Team. In this book, the reader undertakes a metaphorical journey to the stars, which symbolizes top-level interaction and collaboration. The journey is the development from an ordinary management team into a Stellar Management Team, which elevates its operation up to a new level of performance and success."--Provided by publisher.